Critical metals handbook - Gunn, Gus, 1951- (Hoboken, NJ : John Wiley & Sons, 2014)
"The proposed book will provide a unique, one-stop source of information on diverse aspects of the critical metals, including geology, deposits, processing, applications, environmental issues and markets"--Provided by publisher.
"Published in collaboration with the British Geological Survey."
"This work is a co-publication between the American Geophysical Union and Wiley."
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Metals -- Handbooks, manuals, etc; Electronic books